Investigating Effect of Strain and Geometric Defects on Single Polarization Vortex in PbTiO3 Nanowires - Tran, The Quang; Nguyen, Hoang Linh; Nguyen, Van Hoi; Vuong, Van Thanh; Do, Van Truong (JST: Engineering And Technology For Sustainable Development, 2021)
The single polarization vortex structure in nanowire can be used to store binary data in Non-Volatile Ferroelectric Random Access Memories (NVFRAM or FRAM). However, at the nanoscale, mechanical strains or geometry defects (cracks) can affect the polarization vortex and they are one of the reasons to reduce the service life as well as the reliability of the device. In this study, the atomic simulation method using the interactive potential function based on the core-shell model is selected to investigate the effects of strain, cracks and domain wall deviations (DW) on the single polarization vortex in PbTiO3 (PTO) nanowires. The results obtained showed that the polarization vortex can appear or disappear depending on the position and size of the crack. Deviations in the DW position make the polarization vortex change the size and shape. Besides, the magnitude of the vortex investigated increases under tension strain and decreases under compression strain. Especially, in large compression strain (10%), the vortex can be disappeared.